Lichen Sclerosus et Atrophicus Induced by Carbamazepine: A Case Report. (July 2013) - Pranteda, G.; Muscianese, M.; Grimaldi, M.; Fidanza, L.; Pranteda, G.; Narcisi, A.; Nisticò, S.; Bottoni, U.
We report a case of Lichen Sclerosus in a 73-year-old man who had been treated for epilepsy with carbamazepine. Lichen sclerosus et atrophicus (LSA), also called lichen sclerosus (LS), is a chronic inflammatory cutaneous condition characterized by white plaques with epidermal atrophy and scarring. To date no cases of LSA has been linked to carbamazepine, although in a few cases lichenoid eruptions but without sclero-atrophy have been described after exposure to this drug. Therefore, to our knowledge, this is the first report of a Lichen sclerosus et atrophicus induced by carbamazepine